Preoperative serum tissue polypeptide‐specific antigen is a valuable prognostic marker in breast cancer. Issue 4 (7th September 2012) - Ahn, Soo Kyung; Moon, Hyeong‐Gon; Ko, Eunyoung; Kim, Han Suk; Shin, Hee‐Chul; Kim, Jisun; You, Jee Man; Han, Wonshik; Noh, Dong‐Young
Abstract Tissue polypeptide‐specific antigen (TPS), a specific epitope structure of a peptide in serum associated with human cytokeratin 18, is linked to the proliferative activity of tumors. Here, we aimed to identify the association between the preoperative serum TPS level and outcome in breast cancer patients. We assayed preoperative serum TPS levels in 1, 477 breast cancer patients treated between June 2000 and December 2006. The TPS level was measured with a one‐step solid phase radiometric sandwich assay detecting the M3 epitope on cytokeratin 18 fragments. The cutoff value was 80 U/L. Among the 1, 477 breast cancer patients examined, preoperative serum TPS level was elevated (>80 U/L) in 290 patients (19.6%). Age (>45 years), tumor size (>2 cm), nodal metastasis, negative progesterone receptor and human epidermal growth factor receptor 2 were associated with elevated TPS. Evidence of recurrence was observed in 229 patients (15.6%). Elevated TPS was associated with poor disease‐free survival (p < 0.001) and overall survival (p < 0.001). In a multivariate analysis using the Cox proportional regression model, elevated TPS was an independent prognostic factor for disease‐free survival (p = 0.001) and overall survival (p = 0.026). Furthermore, in subgroup analysis based on molecular subtype, the prognostic effect of preoperative TPS on survival (OS: HR 2.614, p = 0.003; DFS: HR 1.895, p = 0.001) was identified only in the luminal A subtype. Elevated preoperative serum TPS level is associated with poor breast cancer outcomes. Based on these findings, we conclude that preoperative TPS is a valuable biomarker for clinical use in predicting outcomes in breast cancer patients.